Reforming Women : The Rhetorical Tactics of the American Female Moral Reform Society, 1834-1854 - Shaver, Lisa J. (Book collections on Project MUSE., 2018)
In Reforming Women, Lisa Shaver locates the emergence of a distinct women's rhetoric and feminist consciousness in the American Female Moral Reform Society. Established in 1834, the society took aim at prostitution, brothels, and the lascivious behavior increasingly visible in America's industrializing cities. In particular, female moral reformers contested the double standard that overlooked promiscuous behavior in men while harshly condemning women for the same offense. Their ardent rhetoric resonated with women across the country. With its widely-read periodical and auxiliary societies representing more than 50,000 women, the American Female Moral Reform Society became the first national reform movement organized, led, and comprised solely by women. Drawing on an in-depth examination of the group's periodical, Reforming Women delineates essential rhetorical tactics including women's strategic use of gender, the periodical press, anger, presence, auxiliary societies, and institutional rhetoric--tactics women's reform efforts would use throughout the nineteenth century. Almost two centuries later, female moral reformers' rhetoric resonates today as our society continues to struggle with different moral expectations for men and women.